A “Universal Struggle for Life”? A Comparative Study of the Regional Reception of Darwinism among Religious Thinkers in the Second Half of the 19th Century - Aellen, Sacha (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2021)
<article class="text-token-text-primary w-full focus:outline-none scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:987ef4bf-0fdb-461d-8b65-60c5e18bd500-26" data-testid="conversation-turn-54" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="eb3dada0-292c-44d0-961e-3eaeee281395" data-message-model-slug="gpt-5-mini"> The present study aims at analyzing the reception of Darwinism among religious intellectuals from the Anglo-Saxon world and the Middle East in the second half of the 19th century. It adopts a comparative approach, understood in its double meaning of individualizing operator and commonality revealer, in order to formulate hypotheses regarding the contextual and the general implications of Darwin’s theory. The main finding is that behind the distinctive politicization of Darwinism that framed the debates towards secularization in one case and towards the relation to the imperial power on the other, the ideas and preoccupations voiced by Anglo-Saxon and Middle Eastern religious thinkers demonstrate striking similarities, with regard to the intensity of the debate, the individuality of the experience, the inscription of Darwinism in the question of modernity, and the types of fundamental questions raised. The overarching idea governing the article is that the relation between religion and Darwinism should not be understood as a necessary opposition. Une « Lutte universelle pour la vie » ? Étude comparative de la réception régionale du Darwinisme parmi les penseurs religieux de la seconde moitié du 19ᵉ siècle Cet article analyse la réception du darwinisme chez les intellectuels religieux dans la seconde moitié du 19ème siècle, dans le monde anglo-saxon et au Moyen-Orient. L’approche comparative, comprise dans sa double signification à la fois comme opératrice d’individualisation et comme révélatrice de similarité, permet de formuler des hypothèses au sujet des implications contextuelles et générales de la théorie de Darwin. La conclusion principale est qu’au-delà du différent mode de politisation du darwinisme, associé à une dynamique de sécularisation d’un côté et à la relation au pouvoir impérial de l’autre, les idées et préoccupations exprimées par les penseurs religieux moyen-orientaux et anglo-saxons démontrent des similitudes frappantes quant à l’intensité du débat, à l’individualité de l’expérience, à l’inscription du darwinisme dans la question de la modernité, et aux types de questions fondamentales soulevées. L’idée qui sous-tend l’article est que la relation entre la religion et le darwinisme ne devrait pas être comprise comme une opposition systématique.